Ղազար Փարպեցու երկերի արևելահայերեն վերջին թարգմանության հանգամանքները - Գուրգեն Մանուկյան (ՀՀ ԳԱԱ հրատ.)
Труды выдающегося историографа и оратора V в. Лазаря Парпеци были изданы в переводе Б. Улубабяна с грабара на восточноармянcкий в 1982 г. издательством Ереванского университета. В этом переводе есть многочисленные неточности историографического и текстологического характера. Иногда это результат грамматических искажений (например, в использовании предлогов) в грабаре. Кроме того, переводчиками не были учтены важные уточнения, внесенные исследователями после публикации текстов историографа в 1904 г. The translations of the works by outstanding historiographer and orator of the 5th century Ghazar Parpetsy from Grabar into Eastern Armenian were published in the translation of B.Ulubabyan by Publishing house of Yerevan State University in 1982. There are many mistakes of historiographical and textological character in the translation. Sometimes it is the result of grammar distortions (eg, in the use of prepositions) in Grabar. Besides, some important corrections done by the investigators after the publication of texts of the historiographers in 1904 were ignored by the translators.
Keywords: History; Philology; Linguistics; Language and Literature; Translation and interpretation; D History